Primary Care in the Workplace: Cost Savings and Improved Health Outcomes - Melondie Carter (Rural Nurse Organization; Binghamton University, 2012)
The major portion of health care dollars is spent on illness care and yet the health outcomes of the United States are poorer than many countries that spend much less. A shift must occur in spending to place more emphasis on prevention. Increasing health promotion and wellness programs in industries is one prevention strategy for decreasing health care costs and improving health outcomes. Although the workplace is a logical site for health promotion, few small employers offer programs and few understand how to balance program costs against benefits. Yet, while at work, the employees are a captive audience and are more likely to engage in wellness activities.